Evolution of Catkins: Inflorescence Morphology of Selected Salicaceae in an Evolutionary and Developmental Context - Cronk, Quentin C. B.; Needham, Isabelle; Rudall, Paula J. (Frontiers in Plant Science, 2015)
Poplars (Populus spp.) and willows (Salix spp.) are well known woody plants common throughout the northern hemisphere, both with fully sequenced genomes. They bear compact unisexual inflorescences known as “catkins”. Closely related genera of the "salicoid clade" within the family Salicaceae include the Asian genera Bennettiodendron, Idesia, Itoa, Poliothyrsis and Carrierea and the Central American genera Olmediella and Macrohasseltia. Like willow and poplar, most of these genera are dioecious, but unlike willow and poplar they generally have loosely branched panicles rather than catkins, and less highly reduced flowers. However the early developing inflorescences of Carrierea and Idesia show similarities to catkins which suggest possible pathways by which the salicoid catkin may have evolved.